Trauma and healing - Perry, Bruce Duncan, 1955-; Linkletter Films; Magna Systems (Barrington, IL : Magna Systems, Inc., 2002)
Explains how adults who suffered trauma in their childhood often have difficulty expressing anger
Medical consultant, Perry Bruce Duncan Perry
Keywords: Post-traumatic stress disorder -- Treatment; Psychophysiology; Psychic trauma -- Treatment